2020
DOI: 10.1002/trc2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Advancing family dementia caregiver interventions in low‐ and middle‐income countries: A pilot cluster randomized controlled trial of Resources for Advancing Alzheimer's Caregiver Health in Vietnam (REACH VN)

Abstract: Introduction Low‐ and middle‐income countries have rapidly increasing numbers of people with dementia, yet little evidence on family caregiving interventions. We tested the preliminary efficacy and feasibility of a family caregiving intervention in northern Vietnam. Methods Nine clusters comprising 60 family caregivers were randomized to a culturally adapted version of a four‐ to six‐session, multicomponent intervention delivered in‐home over 2 to 3 months, or enhanced control. Eligible caregivers were ≥18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Our study is based on thematic analysis of 21 in-depth qualitative interviews conducted with key informants, including family caregivers of persons with dementia, national and local healthcare providers, and community leaders. This study was conducted as part of a larger project as the first step in a process to develop and culturally adapt a family caregiving intervention in Vietnam [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on thematic analysis of 21 in-depth qualitative interviews conducted with key informants, including family caregivers of persons with dementia, national and local healthcare providers, and community leaders. This study was conducted as part of a larger project as the first step in a process to develop and culturally adapt a family caregiving intervention in Vietnam [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most comprehensive multi-component carer intervention is the REACH (Resources for Enhancing Alzheimer’s Caregiver Health) model [ 20 ]. The REACH model was used in Vietnam with preliminary findings showing significant improvement for carer mental health and caregiving burden [ 22 , 36 ]. However, this model is resource-intensive with interventionists going to carers’ home to deliver the intervention over 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The e-DiVA study builds on our team’s prior work and expertise, strengthens and expands existing collaborations between investigators in high-income countries (Australia and the United States) and Vietnam. These include our pilot iSupport adaptation study in Australia [ 14 ] and other studies to develop Vietnam’s National Dementia Plan [ 40 ] and to support Vietnamese dementia family carers [ 41 ]. This project proposal keeps laying the continual foundation for extramural support for both research and capacity-building.…”
Section: Discussionmentioning
confidence: 99%
“…An evidence-based intervention, Resources for Enhancing All Caregivers Health in the Department of Veterans Affairs (REACH VA) [ 17 , 21 ], was adapted in Vietnam and tested in a pilot cluster randomized controlled trial (RCT) of 60 family caregivers [ 22 ], showing strong evidence of feasibility and preliminary efficacy. In this pilot study, caregivers who received the intervention showed significantly lower caregiver burden and psychological distress levels than those in the control group [ 23 ]. This study builds upon our pilot study to test the efficacy of Resources for Enhancing Alzheimer’s Caregiver Health in Vietnam (REACH VN) in a larger cluster RCT embedded in a community setting outside Hanoi using a Phase III clinical trial design [ 24 ].…”
Section: Introductionmentioning
confidence: 99%